Composite current collector, preparation method thereof, battery, battery module and electric device
By setting a transition layer with a gradually changing thermal expansion coefficient between the polymer layer and the metal layer, the interfacial stress problem of the composite current collector during temperature changes is solved, and the high-temperature cycle stability and high-temperature resistance of the battery are improved.
Patent Information
- Application Number
- CN202510927061.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-07-07
AI Technical Summary
The existing composite current collector has large interfacial stress and is prone to stratification when the temperature changes due to the large difference in thermal expansion coefficients between the polymer and the metal, which affects the high-temperature cycle stability of the battery.
A transition layer with a gradually changing thermal expansion coefficient is set between the polymer layer and the metal layer to ensure that the absolute value of the thermal expansion coefficient difference between the two sides of the transition layer and its adjacent layers is ≤4×10-6K. The transition layer is formed by sputtering or spin coating to control the gradient change of the thermal expansion coefficient.
It reduces interfacial stress, prevents peeling, and improves the high-temperature cycle stability and high-temperature resistance of the battery.
Smart Images

Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of battery current collector, in particular to a composite current collector, a preparation method thereof, a battery, a battery module and an electrical equipment. BACKGROUND
[0002] The composite current collector comprises a polymer substrate layer and metal layers on both sides of the substrate layer. Compared with traditional copper-aluminum foil, the composite current collector is lighter in mass, and the battery assembled therefrom has higher energy density. However, due to the large difference in thermal expansion coefficient between the polymer and the metal, stress is easily generated when the temperature changes, resulting in delamination.
[0003] Although many methods have been disclosed in the prior art to reduce the delamination of the composite foil caused by the difference in thermal expansion, the improvement effect is still not ideal, and the deformation under high temperature is still serious. SUMMARY
[0004] The present application provides a composite current collector, which has small interface stress and is not easy to peel off, and is beneficial to improving the cycle stability of the battery.
[0005] The present application provides a preparation method of a composite current collector, and the composite current collector prepared by the method has small interface stress and is not easy to peel off.
[0006] The present application provides a battery, which has excellent high-temperature cycle performance.
[0007] The present application provides a battery module, which has excellent high-temperature resistance.
[0008] The present application provides an electrical equipment, which has excellent high-temperature resistance.
[0009] A first aspect of the present application provides a composite current collector, comprising a polymer layer, a metal layer arranged on at least one side of the polymer layer, and a transition layer between the polymer layer and the metal layer, the thermal expansion coefficient of the transition layer gradually changes along a first direction and satisfies:
[0010] |β1-β 聚合物层 |≤4×10 -6 K,
[0011] |β2-β 金属层 |≤4×10 -6 K,
[0012] wherein β1 is the thermal expansion coefficient of the transition layer on the side close to the polymer layer, β2 is the thermal expansion coefficient of the transition layer on the side close to the metal layer, β 聚合物层 is the thermal expansion coefficient of the polymer layer, and β 金属层 is the thermal expansion coefficient of the metal layer; the first direction is the direction from the polymer layer to the metal layer.
[0013] In the composite current collector, the thermal expansion coefficient of the transition layer on the side close to the polymer layer refers to the thermal expansion coefficient within 0-5 nm from the surface of the polymer layer, and the thermal expansion coefficient of the transition layer on the side close to the metal layer refers to the thermal expansion coefficient within 0-5 nm from the surface of the metal layer.
[0014] In the composite current collector, when the thermal expansion coefficient of the polymer layer is lower than that of the metal layer, the thermal expansion coefficient of the transition layer gradually increases from the side close to the polymer layer to the side close to the metal layer; and when the thermal expansion coefficient of the polymer layer is higher than that of the metal layer, the thermal expansion coefficient of the transition layer gradually decreases from the side close to the polymer layer to the side close to the metal layer.
[0015] In the composite current collector, the total thickness of the transition layer is 10 nm-100 nm.
[0016] In the composite current collector, the material of the transition layer is selected from one or more of magnesium, aluminum, copper, nickel, iron, silver, gold, cobalt, chromium, titanium, molybdenum, tungsten, iron, titanium alloy, zirconium alloy and ceramic.
[0017] In the composite current collector, the material of the polymer layer is one or more of polyethylene, polypropylene, polyethylene terephthalate, polyethylene naphthalate, poly-p-phenylene terephthalamide, polyimide, polycarbonate, polyether ether ketone, polyformaldehyde, poly-p-phenylene sulfide, poly-p-phenylene oxide, polyvinyl chloride, polyamide and polytetrafluoroethylene.
[0018] In the composite current collector, the material of the metal layer is one or more of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum and tungsten.
[0019] In the composite current collector, the thickness of the polymer layer is 2 μm-8 μm.
[0020] In the composite current collector, the thickness of the metal layer is 0.5 μm-2.5 μm.
[0021] The second aspect of the present application provides a preparation method of the composite current collector, and the method specifically comprises the following steps:
[0022] When the thermal expansion coefficient of the polymer layer is lower than that of the metal layer, the method at least comprises the following step: using two or more independent sputtering targets to perform sputtering under different power controls to form the transition layer on the polymer layer.
[0023] When the thermal expansion coefficient of the polymer layer is higher than that of the metal layer, the method at least comprises the following step: using a spin coating method to spin coat raw materials with different concentration ratios to form the transition layer on the polymer layer.
[0024] The third aspect of the present application provides a battery comprising the composite current collector or the composite current collector prepared by the preparation method.
[0025] The fourth aspect of the present application provides a battery module comprising the battery.
[0026] The fifth aspect of the present application provides an electrical equipment comprising the composite current collector or the current collector prepared by the preparation method or the battery module.
[0027] The present application reduces the interface stress of the composite current collector, prevents peeling, and further improves the high-temperature cycle stability of the battery by adding a transition layer with gradually changing thermal expansion coefficient between the polymer layer and the metal layer and limiting the thermal expansion on both sides of the transition layer. DETAILED DESCRIPTION
[0028] To make the skilled in the art better understand the scheme of the present application, the present application is further described in detail below. The following specific embodiments are only to describe the principles and characteristics of the present application, and the examples are only used to explain the present application, not to limit the scope of the present application. Based on the embodiments of the present application, all other embodiments obtained by the skilled in the art without creative labor are within the scope of protection of the present application.
[0029] Based on the existing composite current collector which is prone to stress and delamination due to the large difference in thermal expansion coefficient between the polymer and the metal when the temperature changes, the present application provides a composite current collector comprising a polymer layer, a metal layer arranged on at least one side of the polymer layer, and a transition layer between the polymer layer and the metal layer. The difference between the present application and the prior art is that the thermal expansion coefficient of the transition layer gradually changes along a first direction and satisfies:
[0030] |β1-β 聚合物层 |≤4×10 -6 K,
[0031] |β2-β 金属层 |≤4×10 -6 K,
[0032] Wherein, β1 is the thermal expansion coefficient of the side of the transition layer close to the polymer layer, β2 is the thermal expansion coefficient of the side of the transition layer close to the metal layer, β 聚合物层 is the thermal expansion coefficient of the polymer layer, and β 金属层 is the thermal expansion coefficient of the metal layer.
[0033] The first direction in the above is the direction from the polymer layer to the metal layer.
[0034] The present application adopts a transition layer with gradually changed thermal expansion coefficient, and ensures that the thermal expansion coefficients between the transition layer and the adjacent polymer layer or metal layer on both sides of the transition layer are ≤4×10 -6 K, thereby reducing the interface stress, preventing peeling, and further improving the high-temperature cycle stability of the battery.
[0035] In the above, the thermal expansion coefficient of the transition layer on the side close to the polymer layer and the thermal expansion coefficient of the transition layer on the side close to the metal layer can be detected by the following method:
[0036] The cross-sectional structure of the composite current collector perpendicular to the polymer layer and the metal layer is obtained by ion milling, and then the cross-sectional structure of the entire composite current collector is detected by using an electron microscope. The composition of the position within 0-5nm from the polymer layer or the transition layer is detected and analyzed by energy spectrum, the element composition and content are measured, and the thermal expansion coefficient of the transition layer on the side close to the polymer layer or on the side close to the metal layer is obtained by calculation through a theoretical formula. In detail, the theoretical formula is shown in the following formula (1):
[0037] Formula (1);
[0038] Wherein, α c is the thermal expansion coefficient after mixing, α i is the thermal expansion coefficient of each component, V i is the volume fraction of each component.
[0039] That is, in the above, the thermal expansion coefficient of the transition layer on the side close to the polymer layer refers to the thermal expansion coefficient within 0-5nm from the surface of the polymer layer; and the thermal expansion coefficient of the transition layer on the side close to the metal layer refers to the thermal expansion coefficient within 0-5nm from the surface of the metal layer.
[0040] In the present application, the change trend of the thermal expansion coefficient in the transition layer is not specifically limited, which can be linear change or curve change.
[0041] In some embodiments, when the thermal expansion coefficient of the polymer layer is lower than that of the metal layer, the thermal expansion coefficient of the transition layer gradually increases from the side close to the polymer to the side close to the metal.
[0042] In other embodiments, when the thermal expansion coefficient of the polymer layer is higher than that of the metal layer, the thermal expansion coefficient of the transition layer gradually decreases from the side close to the polymer to the side close to the metal.
[0043] By setting the gradually increasing or gradually decreasing transition layer, the interface stress can be better reduced and peeling can be prevented.
[0044] It should be noted that the gradually increasing or gradually decreasing trend in the above is not specifically limited, which can be gradually increased or decreased in a linear relationship, or gradually increased or decreased in a non-linear relationship.
[0045] Research shows that when the change trend meets the single linear change or the segmented increasing (or decreasing) change of the thermal expansion coefficient of the gradient transition layer along the thickness direction, the interface stress can be better reduced, and peeling can be prevented.
[0046] In the present application, the thickness of the transition layer is not specifically limited, but based on the comprehensive performance of the battery, the thickness of the transition layer is usually kept between 10 nm and 100 nm, that is, the thickness D of the transition layer satisfies 10 nm≤D≤100 nm. Exemplarily, it can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, and any value between any two of the above values.
[0047] In the present application, the material of the transition layer is not specifically limited, which can be metal or non-metal. Exemplarily, it can be one or two of magnesium, aluminum, copper, nickel, iron, silver, gold, cobalt, chromium, titanium, molybdenum, tungsten, iron, titanium alloy, zirconium alloy, or a metal-ceramic composite transition layer, such as nickel and di-aluminum oxide, polymer and silicon dioxide particle composite. Correspondingly, component A can be any one of magnesium, aluminum, copper, nickel, iron, silver, gold, cobalt, chromium, titanium, molybdenum, tungsten, iron, titanium alloy, zirconium alloy, and ceramic.
[0048] In the present application, the material of the polymer layer is not specifically limited, which can be any polymer material that can be used in the composite current collector. Exemplarily, it can be one or more of polyethylene, polypropylene, polyethylene terephthalate, polyethylene naphthalate, poly-para-phenyleneterephthalamide, polyimide, polycarbonate, polyether ether ketone, polyformaldehyde, poly-p-phenylene sulfide, poly-p-phenylene oxide, polyvinyl chloride, polyamide, or polytetrafluoroethylene.
[0049] In the present application, the material of the metal layer is not specifically limited, which can be any metal material that can be used in the composite current collector. Exemplarily, it can be one or more of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum, or tungsten.
[0050] In the present application, the thickness of the polymer layer is not specifically limited, which can be selected according to the conventional selection in the art. Exemplarily, it can be 2 μm-8 μm. For example, it can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, and any value between any two of the above values.
[0051] In the present application, the thickness of the metal layer is not specifically limited and can be selected according to the conventional method in the art. For example, the thickness can be 0.5 μm to 2.5 μm. For example, the thickness can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, or any value between any two of the above values.
[0052] The present application also provides a method for preparing the composite current collector. When the thermal expansion coefficient of the polymer layer is lower than that of the metal layer, the method comprises at least the following step: using two or more independent sputtering targets, sputtering under the control of different power sources, and forming the transition layer on the polymer layer.
[0053] When the thermal expansion coefficient of the polymer layer is higher than that of the metal layer, the method comprises at least the following step: using a spin coating method to spin coat raw materials with different concentration ratios, and forming the transition layer on the polymer layer.
[0054] The composite current collector prepared by the above method has small interface stress, is not easy to peel off, and is beneficial to improving the high-temperature cycle stability of the battery.
[0055] In detail, when the thermal expansion coefficient of the polymer layer is lower than that of the metal layer, the preparation can be performed according to the following method: using two or more independent sputtering targets (for example, metal A and metal B), connecting the sputtering targets to different power sources, respectively, placing the polymer base film on a rotating or translating device between the targets, gradually adjusting the sputtering power of the targets, and adjusting the composition to have a preset concentration distribution. Thus, the thermal expansion coefficient of the transition layer changes according to a preset rule from the side close to the polymer to the side close to the metal, and the absolute value of the difference between the thermal expansion coefficients of the outermost side of the transition layer and the metal layer and the polymer layer is ≤4×10 -6 / K. Then, the metal layer is formed on the side of the transition layer away from the polymer layer by sputtering or evaporation, and the composite current collector is obtained.
[0056] When the thermal expansion coefficient of the polymer layer is higher than that of the metal layer, the preparation can be performed according to the following method: using a spin coating method to spin coat raw materials with different concentration ratios, and forming the transition layer on the polymer base film. When the raw materials are spin coated by the spin coating method, the spin coating is performed according to a preset ratio, so that the thermal expansion coefficient of the transition layer changes according to a preset rule from the side close to the polymer to the side close to the metal, and the absolute value of the difference between the thermal expansion coefficients of the outermost side of the transition layer and the metal layer and the polymer layer is ≤4×10 -6 / K. Then, the metal layer is formed on the side of the transition layer away from the polymer layer by sputtering or evaporation, and the composite current collector is obtained.
[0057] The type of the current collector in the present application is not specifically limited, and the current collector can be a positive electrode current collector or a negative electrode current collector.
[0058] The application also provides a battery comprising the current collector or the current collector prepared by the preparation method. Based on the same reasons, the battery has good high-temperature cycle performance.
[0059] In the above, the type of the battery is not specifically limited, such as a lithium battery, a sodium battery, or a potassium battery, etc. In addition, it can be a liquid battery, a full solid battery, or a quasi solid battery, and it can be a primary battery or a secondary battery.
[0060] The specific type of the battery of the application is not specifically limited, for example, from the perspective of shape, the battery includes but is not limited to a square cell, a soft pack battery, and a cylindrical battery, etc. From the perspective of the pole core structure, the pole core of the battery can be a wound pole core (i.e., the positive pole sheet, the negative pole sheet, and the separator are stacked and then the pole core is prepared by a winding process), or a laminated pole core (i.e., a plurality of positive pole sheets, negative pole sheets, and separators are stacked to form a pole core). The shell can be a hard shell (such as a steel shell, a hard plastic shell, etc.), or a soft shell (such as an aluminum plastic film, a bag type soft shell, etc.), etc.
[0061] The preparation method of the battery of the application is not specifically limited, for example, it can be prepared according to the following method: first, the positive current collector and the negative current collector are prepared according to the above method, then the active material layer is prepared on the positive current collector and the negative current collector respectively to obtain the positive pole sheet and the negative pole sheet, and then the positive pole sheet, the negative pole sheet, and the separator are assembled and then the electrolyte is injected to obtain the battery.
[0062] When the positive pole sheet and the negative pole sheet are prepared, for example, the active material, the conductive agent, and the binder can be dispersed in an appropriate amount of N-methyl pyrrolidone (NMP) solvent, and then fully stirred and mixed to form a uniform slurry; the slurry is uniformly coated on the composite current collector, and then dried, rolled, and cut to obtain the pole sheet.
[0063] The positive active material can be selected from commonly used positive materials of batteries such as nickel cobalt manganese oxide (NCM), nickel cobalt aluminum oxide (NCA), or lithium iron phosphate (LFP), etc. The negative active material can be selected from natural graphite, artificial graphite, or other new type of negative materials such as silicon-based materials. The conductive material can generally use carbon black (such as SuperP) and carbon nanotubes to enhance the conductivity of the electrode. The binder can be selected from polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, a polymer containing an oxirane, polyvinyl pyrrolidone, polyurethane, etc.
[0064] The single-sided coating thickness is generally controlled to be 50-300 μm, the electrode sheet after coating is placed in a drying device to remove the solvent to obtain a dried electrode, and a compaction device is used to compact the dried electrode sheet to improve the density and conductivity of the electrode.
[0065] The electrolyte can be a conventional electrolyte in the art, for example, the electrolyte is a non-aqueous electrolyte, which can specifically include an organic solvent, an additive, and an electrolyte salt, the organic solvent can include one or more of ethylene carbonate (EC), diethyl carbonate (DEC), and propylene carbonate (PC), the additive can include fluoroethylene carbonate (FEC), the additive can include vinylene carbonate (VC), and the electrolyte salt can include a lithium salt, for example, lithium hexafluorophosphate (LiPF6), but is not limited thereto.
[0066] The separator is used to separate the positive electrode sheet and the negative electrode sheet to avoid short circuit caused by contact between the positive electrode sheet and the negative electrode sheet, and the present application can use a conventional separator in the art, which is not particularly limited. For example, the separator material can be a separator made of one or more of high-density polyethylene, ultra-high-density polyethylene, low-density polyethylene, linear low-density polyethylene, high-density polypropylene, ultra-high-density polypropylene, polyimide, and polyvinylidene fluoride.
[0067] In the embodiments of the present application, the battery cell can be packaged with a conventional casing material in the art, and the casing can include a soft packaging material such as an aluminum plastic film, but is not limited thereto.
[0068] The positive electrode sheet, the separator, and the negative electrode sheet can be assembled into a battery by a conventional method in the art. For example, the positive electrode sheet, the separator, and the negative electrode sheet can be arranged in an interleaved and stacked manner to obtain a jelly-roll type battery cell (or a winding type battery cell). Then, the battery cell is placed in a casing (an outer package), and after conventional processes such as liquid injection (i.e., electrolyte injection) and packaging, a battery is obtained.
[0069] The present application also provides a battery module, which includes the battery described above, and the number of battery cells contained therein can be one or more, and the specific number can be selected by a person skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery module can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by a person skilled in the art according to the application and capacity of the battery pack.
[0070] The present application also provides an electric device, which includes the battery described above. The electric device can be a conventional electric device in the art, including consumer electronics (mobile communication devices, notebook computers, tablet computers, wearable devices, etc.), unmanned aerial vehicles, power tools, energy storage devices, electric bicycles, electric vehicles, etc.
[0071] The composite current collector described in the present application will be described in detail below in conjunction with specific embodiments.
[0072] Embodiment 1
[0073] The embodiment provides a battery, comprising a positive electrode current collector and a negative electrode current collector, wherein the positive electrode current collector and the negative electrode current collector are both composite current collectors.
[0074] (1) Negative electrode current collector
[0075] The negative electrode current collector comprises a first copper layer, a first transition layer, a polymer layer, a second transition layer and a second copper layer in sequence. -6 The first copper layer and the second copper layer have a thickness of 1 μm, and a thermal expansion coefficient of 17×10 -6 / K.
[0076] The first transition layer and the second transition layer are made of Ni and Cr, and have a thickness of 50 nm. -6 The first transition layer and the second transition layer have a thermal expansion coefficient of 13×10 -6 / K and 6×10 -6 / K, respectively. -6 The thermal expansion coefficient of the first transition layer and the second transition layer changes from 6.35×10
[0077] The specific preparation method is as follows: a magnetron sputtering system is used, and independent Ni and Cr targets are arranged, and the substrate can be rotated or moved.
[0078] Pre-sputtering cleaning: the Ni and Cr targets are respectively pre-sputtered for 5 minutes to remove surface oxides.
[0079] Initial stage: the power of the Cr target is 95%, the power of the Ni target is 5%, the substrate temperature is controlled to be less than or equal to 100 ℃, the vacuum condition is that the background vacuum is less than or equal to 1×10 -6 Torr, the sputtering gas is high-purity argon (Ar), the working pressure is 3 mTorr, the PI is deposited on both sides, and the deposition is stopped when the thickness is 5 nm.
[0080] Gradient layer: linearly reduce the power of the Cr target and increase the power of the Ni target (specifically: the power of the Cr target is attenuated from 90% to 20% at a power of 10%, and the power of the Ni target is increased from 10% to 80% at a power of 10%), continue sputtering on the layer sputtered in the initial stage, stop sputtering 5 nm each time, and wait for the temperature to reduce to below 100 ℃.
[0081] End stage: continue sputtering on the layer sputtered above, the power of the Ni target is 100%, and the power of the Cr target is 0%, to form a 5 nm Ni-rich layer.
[0082] Thickness monitoring: The total thickness was strictly controlled at 50 ± 5 nm by real-time monitoring with a quartz crystal microbalance.
[0083] (2) Positive electrode current collector
[0084] The positive electrode current collector also comprises a first aluminum layer, a first transition layer, a polymer layer, a second transition layer, and a second aluminum layer in sequence. The thickness of the first aluminum layer and the second aluminum layer is 1 μm, and the thermal expansion coefficient thereof is 23 x 10 -6 / K; the material of the intermediate polymer layer is polyimide (PI), the thickness thereof is 8 μm, and the thermal expansion coefficient thereof is 3 x 10 -6 / K.
[0085] The materials of the first transition layer and the second transition layer are Al and Cr, and the thicknesses thereof are both 50 nm. The thermal expansion coefficient of Al is 23 x 10 -6 / K, and the thermal expansion coefficient of Cr is 6 x 10 -6 / K. The thermal expansion coefficient of the first transition layer and the second transition layer changes from 6.85 x 10 -6 / K close to the polymer side to 23 x 10 -6 / K close to the metal side.
[0086] The specific preparation method is as follows:
[0087] A magnetron sputtering system is used, which is equipped with independent Al and Cr targets, and the substrate can be rotated or moved. The deposition speed of the Al and Ni targets is calibrated in advance to ensure that the deposition speed of the two is consistent, and the power at this time is set to 100% of the respective target material.
[0088] Pre-sputtering cleaning: pre-sputter the Al and Cr targets for 5 minutes respectively to remove surface oxides.
[0089] Initial stage: Al target power 95%, Ni target power 5%, control substrate temperature ≤ 100℃, vacuum condition: background vacuum ≤ 1 x 10 -6 Torr, sputtering gas is high-purity argon (Ar), working gas pressure is 3 mTorr, deposit on both sides of PI, stop when the deposition thickness is 5 nm.
[0090] Gradient layer: linearly reduce the Cr power and increase the Al power (specifically: the Cr target power decays from 90% to 20% at a power decay of 10%, and the Al target power increases from 10% to 80% at a power increase of 10%), continue sputtering on the layer sputtered in the initial stage, stop each time 5 nm, and wait for the temperature to decrease to below 100℃.
[0091] End stage: continue sputtering on the layer sputtered above, Al target power 100%, Cr target power 0%, form a 5 nm Al-rich layer.
[0092] Thickness monitoring: The total thickness was strictly controlled at 50±5 nm by real-time monitoring with a quartz crystal microbalance.
[0093] (3) Battery production
[0094] Dissolve lithium iron phosphate, carbon black and polyvinylidene fluoride in a proper amount of N-methyl pyrrolidone (NMP) solvent according to the mass ratio of 94:3:3, fully stir and mix to form a uniform positive electrode slurry, coat the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet;
[0095] Dissolve artificial graphite, sodium carboxymethyl cellulose and conductive carbon black in a proper amount of N-methyl pyrrolidone (NMP) solvent according to the mass ratio of 94:3:3, fully stir and mix to form a uniform negative electrode slurry, coat the negative electrode slurry on the negative electrode current collector to obtain a negative electrode sheet.
[0096] Put the coated electrode sheet into a drying device to remove the solvent and obtain a dried electrode. Use a compaction device to compact the dried electrode sheet.
[0097] Stack the positive electrode sheet, the separator and the negative electrode sheet to prepare a battery core. Put the assembled battery core into a battery shell and inject 1 mol / L lithium hexafluorophosphate electrolyte (the solvent is prepared by mixing ethylene carbonate and diethyl carbonate at a volume ratio of 1:1) to obtain a battery.
[0098] Example 2
[0099] The present embodiment provides a battery including a positive electrode current collector and a negative electrode current collector, wherein both the positive electrode current collector and the negative electrode current collector are composite current collectors. The difference between the present embodiment and Example 1 is that the positive electrode current collector does not contain a transition layer.
[0100] (1) Negative electrode current collector
[0101] The negative electrode current collector includes a first copper layer, a first transition layer, a polymer layer, a second transition layer and a second copper layer in sequence. The thickness of the first copper layer and the second copper layer is 1 μm, and the thermal expansion coefficient thereof is 17×10 -6 / K; the material of the intermediate polymer layer is polyimide (PI), and the thickness thereof is 4 μm, and the thermal expansion coefficient thereof is 3×10 -6 / K.
[0102] The materials of the first transition layer and the second transition layer are Ni and Cr, and the thicknesses thereof are both 50 nm. The thermal expansion coefficient of Ni is 13×10 -6 / K, and the thermal expansion coefficient of Cr is 6×10 -6 / K. The thermal expansion coefficient of the first transition layer and the second transition layer changes from 6.35×10 -6 / K close to the polymer side to 13×10 -6 / K.
[0103] The specific preparation method is as follows:
[0104] A magnetron sputtering system is used, which is equipped with independent Ni and Cr targets, and the substrate can be rotated or moved. The deposition rates of the Cr and Ni targets are calibrated in advance to ensure that the deposition rates of the two are consistent, and at this time the power is positioned at 100% of the respective target materials.
[0105] Pre-sputtering cleaning: pre-sputter the Ni and Cr targets for 5 minutes respectively to remove surface oxides.
[0106] Initial stage: Cr target power 95%, Ni target power 5%, control substrate temperature ≤100℃, vacuum condition: background vacuum ≤1×10 -6 Torr, sputtering gas is high-purity argon (Ar), working pressure is 3 mTorr, deposit on both sides of PI, stop when the deposition thickness is 5 nm.
[0107] Gradient layer: linearly reduce Cr power and increase Ni power (specifically: Cr target power from 90% decays by 10% to 20%, Ni target power from 10% grows by 10% to 80%), continue sputtering on the layer sputtered in the initial stage, stop each time 5 nm, and wait for the temperature to drop below 100℃.
[0108] End stage: continue sputtering on the layer sputtered above, Ni target power 100%, Cr target power 0%, form a 5 nm Ni-rich layer.
[0109] Thickness monitoring: real-time monitoring by quartz crystal microbalance, total thickness strictly controlled at 50±5 nm.
[0110] (2) Positive current collector
[0111] The positive current collector also includes a first aluminum layer, a polymer layer, and a second aluminum layer in sequence. The thickness of the first aluminum layer and the second aluminum layer is 1 μm, and the thermal expansion coefficient is 23×10 -6 / K; the material of the intermediate polymer layer is polyimide (PI), the thickness is 8 μm, and the thermal expansion coefficient is 3×10 -6 / K.
[0112] (3) Cell production
[0113] Dissolve lithium iron phosphate, carbon black, and polyvinylidene fluoride in a mass ratio of 94:3:3 in an appropriate amount of N-methyl pyrrolidone (NMP) solvent, mix thoroughly to form a uniform positive electrode slurry, and coat the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet;
[0114] Artificial graphite, sodium carboxymethyl cellulose, and conductive carbon black were dissolved in an appropriate amount of N-methylpyrrolidone (NMP) solvent at a mass ratio of 94:3:3, and the mixture was fully stirred to form a uniform negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector to obtain a negative electrode sheet.
[0115] The coated electrode sheet is placed in a drying device to remove the solvent to obtain a dried electrode, and the dried electrode sheet is compacted using a compacting device.
[0116] The positive electrode sheet, separator, and negative electrode sheet are stacked to form a battery core, the assembled battery core is placed in a battery shell, and a 1 mol / L lithium hexafluorophosphate (solvent is ethylene carbonate and diethyl carbonate prepared in a volume ratio of 1:1) electrolyte is injected to obtain a battery.
[0117] Example 3
[0118] This embodiment provides a battery, including a positive electrode current collector and a negative electrode current collector, wherein both the positive electrode current collector and the negative electrode current collector are composite current collectors.
[0119] (1) Negative electrode current collector
[0120] The negative electrode current collector includes a first copper layer, a first transition layer, a polymer layer, a second transition layer, and a second copper layer in sequence. The thickness of the first copper layer and the second copper layer are both 1 μm, and their thermal expansion coefficient is 17×10 -6 / K; the material of the middle polymer layer is polyethylene terephthalate (PET), with a thickness of 4 μm and a thermal expansion coefficient of 70×10 -6 / K.
[0121] The materials of the first transition layer and the second transition layer are PET and SiO2, with a thickness of 100 nm. The thermal expansion coefficient of SiO2 is 0.5×10 -6 / K. The thermal expansion coefficients of the first transition layer and the second transition layer are both 66.5×10 -6 / K changes to 14.4×10 close to the metal side -6 / K.
[0122] The specific preparation method is as follows:
[0123] Disperse SiO2 in ethanol, add 1.5wt% KH-550 coupling agent, sonicate for 1 hour, reflux at 70°C for 8 hours, and centrifuge until the pH is neutral. Prepare the following solution using hexafluoroisopropanol (HFIP) and tetrahydrofuran (THF) in a 7:3 volume ratio as solvents:
[0124] Solution A: PET solution (0.3wt% PET, HFIP / THF solvent)
[0125] B liquid: SiO2 / PET mixed solution (SiO2 volume fraction is 80%)
[0126] The flow rate of A and B liquid was controlled to change the gradient using a microfluidic chip.
[0127] Initial stage: the flow rate ratio of A liquid to B liquid was 1:4.5 (the volume fraction of SiO2 was 5%), and after mixing, it was spin-coated on the PET base film at a rotation speed of 2000 rpm for 20 s, with a thickness of 20 nm.
[0128] Gradient layer: the microfluidic mixing ratio was adjusted synchronously, and the volume fraction of SiO2 was controlled to be 10%, 20%, 40%, and 60% in turn. The mixed solution was spin-coated on the initial spin-coated layer, with an initial rotation speed of 3000 rpm, linearly accelerated to 8000 rpm at an acceleration rate of 200 rpm / s, and each spin-coated for 20 nm and stopped, and the coated film was dried.
[0129] End stage: continue to spin-coat B liquid on the spin-coated layer, with an initial rotation speed of 3000 rpm, linearly accelerated to 8000 rpm at an acceleration rate of 200 rpm / s, and controlled to a thickness of 20 nm.
[0130] (2) Positive current collector
[0131] The positive current collector also includes a first aluminum layer, a first transition layer, a polymer layer, a second transition layer, and a second aluminum layer in turn. The thickness of the first aluminum layer and the second aluminum layer is 1 μm, and the thermal expansion coefficient is 23×10 -6 / K; the material of the intermediate polymer layer is polyethylene terephthalate (PET), the thickness is 8 μm, and the thermal expansion coefficient is 70×10 -6 / K.
[0132] The materials of the first transition layer and the second transition layer are PET and SiO2, and the thickness is 100 nm. The thermal expansion coefficient of SiO2 is 0.5×10 -6 / K. The thermal expansion coefficients of the first transition layer and the second transition layer change from 66.5×10 -6 / K close to the polymer side to 21.4×10 -6 / K close to the metal side.
[0133] The specific preparation method is as follows:
[0134] SiO2 was dispersed in ethanol, 1.5wt% KH-550 coupling agent was added, ultrasonic treatment was performed for 1 hour, 70°C reflux reaction was performed for 8 hours, and centrifugal washing was performed until the pH was neutral. The following solution was prepared using hexafluoroisopropanol (HFIP):tetrahydrofuran (THF) as the solvent in a volume ratio of 7:3:
[0135] A liquid: pure PET solution (0.3wt% PET, HFIP / THF solvent)
[0136] B liquid: SiO2 / PET mixed solution (SiO2 volume fraction is 70%)
[0137] The flow rate of A and B liquid was controlled to change the gradient using a microfluidic chip.
[0138] Initial stage: the flow rate ratio of A liquid to B liquid was 1:3 (the volume fraction of SiO2 was 5%), and after mixing, it was spin-coated on the PET base film at a rotation speed of 2000 rpm for 20 s, with a thickness of 20 nm.
[0139] Gradient layer: the microfluidic mixing ratio was adjusted synchronously, and the volume fraction of SiO2 was controlled to be 10%, 15%, 30%, and 50% in turn. The mixed solution was spin-coated on the initial spin-coated layer, with an initial rotation speed of 3000 rpm, linearly accelerated to 8000 rpm at an acceleration rate of 200 rpm / s, and each spin-coated for 20 nm and stopped, waiting for the coating film to dry.
[0140] End stage: continue to spin-coat B liquid on the spin-coated layer, with an initial rotation speed of 3000 rpm, linearly accelerated to 8000 rpm at an acceleration rate of 200 rpm / s, and controlled to a thickness of 20 nm.
[0141] (3) Battery production
[0142] Dissolve lithium iron phosphate, carbon black, and polyvinylidene fluoride in a mass ratio of 94:3:3 in an appropriate amount of N-methyl pyrrolidone (NMP) solvent, mix thoroughly to form a uniform positive electrode slurry, and coat the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet.
[0143] Dissolve artificial graphite, sodium carboxymethyl cellulose, and conductive carbon black in a mass ratio of 94:3:3 in an appropriate amount of N-methyl pyrrolidone (NMP) solvent, mix thoroughly to form a uniform negative electrode slurry, and coat the negative electrode slurry on the negative electrode current collector to obtain a negative electrode sheet.
[0144] Place the coated electrode sheet into a drying device to remove the solvent and obtain a dried electrode. Use a compaction device to compact the dried electrode sheet.
[0145] Stack the positive electrode sheet, separator, and negative electrode sheet to prepare a battery core. Place the assembled battery core into a battery shell and inject 1 mol / L lithium hexafluorophosphate electrolyte (solvent is a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) to obtain a battery.
[0146] Comparative Example 1
[0147] The comparative example 1 provides a battery including a positive electrode current collector and a negative electrode current collector, wherein both the positive electrode current collector and the negative electrode current collector are composite current collectors, which are different from the example 1 in that no transition layer is included.
[0148] (1) Negative electrode current collector
[0149] The negative electrode current collector includes a first copper layer, a polymer layer, and a second copper layer in sequence. The thickness of the first copper layer and the second copper layer is 1 μm, and the thermal expansion coefficient thereof is 17 x 10 -6 / K; the material of the intermediate polymer layer is polyimide (PI), the thickness thereof is 4 μm, and the thermal expansion coefficient thereof is 3 x 10 -6 / K.
[0150] (2) Positive electrode current collector
[0151] The positive electrode current collector also includes a first aluminum layer, a polymer layer, and a second aluminum layer in sequence. The thickness of the first aluminum layer and the second aluminum layer is 1 μm, and the thermal expansion coefficient thereof is 23 x 10 -6 / K; the material of the intermediate polymer layer is polyimide (PI), the thickness thereof is 8 μm, and the thermal expansion coefficient thereof is 3 x 10 -6 / K.
[0152] (3) Battery production
[0153] Dissolve lithium iron phosphate, carbon black, and polyvinylidene fluoride in a proper amount of N-methyl pyrrolidone (NMP) solvent according to the mass ratio of 94:3:3, fully stir and mix to form a uniform positive electrode slurry, coat the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet;
[0154] Dissolve artificial graphite, sodium carboxymethyl cellulose, and conductive carbon black in a proper amount of N-methyl pyrrolidone (NMP) solvent according to the mass ratio of 94:3:3, fully stir and mix to form a uniform negative electrode slurry, coat the negative electrode slurry on the negative electrode current collector to obtain a negative electrode sheet.
[0155] Put the coated electrode sheet into a drying device to remove the solvent, and obtain a dried electrode. Use a compaction device to compact the dried electrode sheet.
[0156] Use the positive electrode sheet, the separator, and the negative electrode sheet to prepare a battery core in a lamination manner, put the assembled battery core into a battery shell, inject 1 mol / L lithium hexafluorophosphate electrolyte (the solvent is prepared by mixing ethylene carbonate and diethyl carbonate according to a volume ratio of 1:1), and obtain a battery.
[0157] Comparative example 2
[0158] The comparative example 3 provides a battery including a positive electrode current collector and a negative electrode current collector, wherein both the positive electrode current collector and the negative electrode current collector are composite current collectors, which is different from the example 3 in that no transition layer is included.
[0159] (1) Negative electrode current collector
[0160] The negative electrode current collector includes a first copper layer, a polymer layer, and a second copper layer in sequence. The thickness of the first copper layer and the second copper layer is 1 μm, and the thermal expansion coefficient thereof is 17 x 10 -6 / K; the material of the intermediate polymer layer is polyethylene terephthalate (PET), the thickness thereof is 4 μm, and the thermal expansion coefficient thereof is 70 x 10 -6 / K.
[0161] (2) Positive electrode current collector
[0162] The positive electrode current collector also includes a first aluminum layer, a polymer layer, and a second aluminum layer in sequence. The thickness of the first aluminum layer and the second aluminum layer is 1 μm, and the thermal expansion coefficient thereof is 23 x 10 -6 / K; the material of the intermediate polymer layer is polyethylene terephthalate (PET), the thickness thereof is 8 μm, and the thermal expansion coefficient thereof is 70 x 10 -6 / K.
[0163] (3) Battery production
[0164] Lithium iron phosphate, carbon black, and polyvinylidene fluoride are dissolved in an appropriate amount of N-methyl pyrrolidone (NMP) solvent according to a mass ratio of 94:3:3, and are fully stirred and mixed to form a uniform positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector to obtain a positive electrode sheet.
[0165] Artificial graphite, sodium carboxymethyl cellulose, and conductive carbon black are dissolved in an appropriate amount of N-methyl pyrrolidone (NMP) solvent according to a mass ratio of 94:3:3, and are fully stirred and mixed to form a uniform negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector to obtain a negative electrode sheet.
[0166] The coated electrode sheet is placed in a drying device to remove the solvent, and a dried electrode is obtained. The dried electrode sheet is compacted using a compaction device.
[0167] The positive electrode sheet, the separator, and the negative electrode sheet are prepared into a battery core in a lamination manner. The assembled battery core is placed in a battery shell, and 1 mol / L lithium hexafluorophosphate (solvent: prepared by mixing ethylene carbonate and diethyl carbonate at a volume ratio of 1:1) electrolyte is injected, and a battery is obtained.
[0168] Comparative example 3
[0169] The comparative example provides a battery including a positive electrode current collector and a negative electrode current collector, wherein the positive electrode current collector and the negative electrode current collector are both composite current collectors, which are different from example 1 in that the thermal expansion coefficient of the transition layer is not gradually changed.
[0170] (1) Negative electrode current collector
[0171] The negative electrode current collector includes a first copper layer, a first transition layer, a polymer layer, a second transition layer, and a second copper layer in sequence. The thickness of the first copper layer and the second copper layer is 1 μm, and the thermal expansion coefficient thereof is 17×10 -6 / K; the material of the intermediate polymer layer is polyimide (PI), the thickness thereof is 4 μm, and the thermal expansion coefficient thereof is 3×10 -6 / K.
[0172] The material of the first transition layer and the second transition layer is Ni, and the thickness thereof is 50 nm, wherein the thermal expansion coefficient of Ni is 13×10 -6 / K.
[0173] (2) Positive electrode current collector
[0174] The positive electrode current collector also includes a first aluminum layer, a first transition layer, a polymer layer, a second transition layer, and a second aluminum layer in sequence. The thickness of the first aluminum layer and the second aluminum layer is 1 μm, and the thermal expansion coefficient thereof is 23×10 -6 / K; the material of the intermediate polymer layer is polyimide (PI), the thickness thereof is 8 μm, and the thermal expansion coefficient thereof is 3×10 -6 / K.
[0175] The material of the first transition layer and the second transition layer is Al and Cr, and the thickness thereof is 50 nm, wherein the thermal expansion coefficient of Al is 23×10 -6 / K, the thermal expansion coefficient of Cr is 6×10 -6 / K, the volume fraction of Al is 80%, and the volume fraction of Cr is 20%.
[0176] (3) Battery production
[0177] Lithium iron phosphate, carbon black, and polyvinylidene fluoride are dissolved in an appropriate amount of N-methyl pyrrolidone (NMP) solvent according to a mass ratio of 94:3:3, and are fully stirred and mixed to form a uniform positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector to obtain a positive electrode sheet.
[0178] Artificial graphite, sodium carboxymethyl cellulose, and conductive carbon black are dissolved in an appropriate amount of N-methyl pyrrolidone (NMP) solvent according to a mass ratio of 94:3:3, and are fully stirred and mixed to form a uniform negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector to obtain a negative electrode sheet.
[0179] The coated electrode sheet is placed in a drying device to remove the solvent, and a dried electrode is obtained. The dried electrode sheet is compacted using a compaction device.
[0180] The positive electrode sheet, the separator, and the negative electrode sheet are stacked to form a battery core. The assembled battery core is placed in a battery shell, and 1 mol / L lithium hexafluorophosphate electrolyte (solvent: ethylene carbonate and diethyl carbonate, prepared in a volume ratio of 1:1) is injected to obtain a battery.
[0181] Comparative Example 4
[0182] This comparative example provides a battery including a positive current collector and a negative current collector, wherein both the positive current collector and the negative current collector are composite current collectors, and the difference from Example 3 is that the thermal expansion coefficients of the transition layers are not gradually changed.
[0183] (1) Negative current collector
[0184] The negative current collector includes, in sequence, a first copper layer, a first transition layer, a polymer layer, a second transition layer, and a second copper layer. The thickness of the first copper layer and the second copper layer is 1 μm, and the thermal expansion coefficient thereof is 17×10 -6 / K; the material of the intermediate polymer layer is polyethylene terephthalate (PET), the thickness thereof is 4 μm, and the thermal expansion coefficient thereof is 70×10 -6 / K.
[0185] The materials of the first transition layer and the second transition layer are SiO2+PET, and the thickness thereof is 100 nm. The thermal expansion coefficient of SiO2 is 0.5×10 -6 / K, the thermal expansion coefficient of PET is 70×10 -6 / K, the volume fraction of SiO2 is 5%, and the volume fraction of PET is 95%. The thermal expansion coefficient of 5% SiO2+95% PET is 66.5×10 -6 / K.
[0186] (2) Positive current collector
[0187] The positive current collector also includes, in sequence, a first aluminum layer, a first transition layer, a polymer layer, a second transition layer, and a second aluminum layer. The thickness of the first aluminum layer and the second aluminum layer is 1 μm, and the thermal expansion coefficient thereof is 23×10 -6 / K; the material of the intermediate polymer layer is polyethylene terephthalate (PET), the thickness thereof is 8 μm, and the thermal expansion coefficient thereof is 70×10 -6 / K.
[0188] The materials of the first transition layer and the second transition layer are SiO2+PET, and the thickness thereof is 100 nm. The thermal expansion coefficient of SiO2 is 0.5×10 -6 / K, the thermal expansion coefficient of PET is 70*10 -6 / K, the thermal expansion coefficient of 5% SiO2+95% PET is 66.5*10 -6 / K.
[0189] (3) Battery production
[0190] Dissolve lithium iron phosphate, carbon black, and polyvinylidene fluoride in a mass ratio of 94:3:3 in an appropriate amount of N-methyl pyrrolidone (NMP) solvent, fully stir and mix to form a uniform positive electrode slurry, coat the positive electrode slurry on the positive electrode current collector to obtain a positive electrode sheet;
[0191] Dissolve artificial graphite, sodium carboxymethyl cellulose, and conductive carbon black in a mass ratio of 94:3:3 in an appropriate amount of N-methyl pyrrolidone (NMP) solvent, fully stir and mix to form a uniform negative electrode slurry, coat the negative electrode slurry on the negative electrode current collector to obtain a negative electrode sheet.
[0192] Place the coated electrode sheet into a drying device to remove the solvent and obtain a dried electrode. Use a compaction device to compact the dried electrode sheet.
[0193] Stack the positive electrode sheet, separator, and negative electrode sheet to prepare a battery core. Place the assembled battery core into a battery shell and inject 1 mol / L lithium hexafluorophosphate electrolyte (solvent is ethylene carbonate and diethyl carbonate prepared in a volume ratio of 1:1) to obtain a battery.
[0194] High-temperature cycle performance test:
[0195] Test the prepared battery after standing at 25°C, 45°C, and 60°C for 8 hours, respectively. Test 5 batteries in each group and record the average value of the capacity retention rate after 500 cycles. The results are shown in Table 1 below.
[0196]
Capacity retention rate test
[0197] Test the batteries treated at different temperatures according to the following methods:
[0198] (1) Charging: charge at a current of 1C to 3.8V, stand for 10min;
[0199] (2) Discharging: discharge at a current of 1C to 2.0V, stand for 10min;
[0200] (3) After 500 cycles, record the ratio of the capacity to the initial capacity, which is the capacity retention rate after 500 cycles.
[0201] Table 1 Cycle capacity retention rate
[0202]
[0203] From the above results, it can be seen that the high-temperature cycle performance of the batteries prepared in Example 1 at 60℃ is better than that of Comparative Examples 1 and 3, and the high-temperature cycle performance of the batteries prepared in Example 3 at 60℃ is better than that of Comparative Examples 2 and 4, indicating that the composite current collector provided by the application is conducive to improving the high-temperature cycle performance of the battery.
[0204] Finally, it should be noted that: other embodiments of the application will be readily apparent to those skilled in the art with the consideration of the specification and practice of the application disclosed herein. The application is intended to cover any variations, uses or adaptive changes of the application that follow the general principles of the application and include common knowledge or conventional technical means in the art that are not disclosed by the application, and are not limited to the above description, and various modifications and changes can be made without departing from the scope thereof. The scope of the application is only limited by the appended claims.
Claims
1. A composite current collector, characterized in that: The invention comprises a polymer layer, a metal layer provided on at least one side of the polymer layer, and a transition layer between the polymer layer and the metal layer, wherein the thermal expansion coefficient of the transition layer gradually changes along a first direction and satisfies: |β1-β 聚合物层 |≤4×10 -6 K, |β2-β 金属层 |≤4×10 -6 K, Among them, β1 is the thermal expansion coefficient of the transition layer close to the polymer layer, β2 is the thermal expansion coefficient of the transition layer close to the metal layer, and β 聚合物层 is the thermal expansion coefficient of the polymer layer, β 金属层 is the thermal expansion coefficient of the metal layer; the first direction is the direction from the polymer layer to the metal layer; The thermal expansion coefficient of the transition layer close to the polymer layer refers to the thermal expansion coefficient of the transition layer within 0-5nm from the surface of the polymer layer; the thermal expansion coefficient of the transition layer close to the metal layer refers to the thermal expansion coefficient of the transition layer within 0-5nm from the surface of the metal layer; When the thermal expansion coefficient of the polymer layer is lower than that of the metal layer, the thermal expansion coefficient of the transition layer gradually increases from the side close to the polymer layer to the side close to the metal layer; when the thermal expansion coefficient of the polymer layer is higher than that of the metal layer, the thermal expansion coefficient of the transition layer gradually decreases from the side close to the polymer layer to the side close to the metal layer.
2. The composite current collector according to claim 1, characterized in that The total thickness of the transition layer is 10nm-100nm.
3. The composite current collector according to claim 1 or 2, characterized in that: The material of the transition layer is selected from one or more of magnesium, aluminum, copper, nickel, iron, silver, gold, cobalt, chromium, titanium, molybdenum, tungsten, iron, titanium alloy, zirconium alloy, and ceramics.
4. The composite current collector according to claim 1 or 2, characterized in that: The material of the polymer layer is one or more of polyethylene, polypropylene, polyethylene terephthalate, polyethylene naphthalate, poly(p-phenylene terephthalamide), polyimide, polycarbonate, polyetheretherketone, polyoxymethylene, poly(p-phenylene sulfide), poly(p-phenylene oxide), polyvinyl chloride, polyamide or polytetrafluoroethylene; and / or The material of the metal layer is one or more of aluminum, copper, nickel, iron, titanium, silver, gold, cobalt, chromium, molybdenum or tungsten.
5. The composite current collector according to claim 1 or 2, characterized in that: The thickness of the polymer layer is 2 μm to 8 μm; and / or The thickness of the metal layer is 0.5 μm-2.5 μm.
6. A method for preparing the composite current collector according to any one of claims 1 to 5, characterized in that: When the thermal expansion coefficient of the polymer layer is lower than that of the metal layer, the method at least includes the steps of: using two or more independent sputtering targets to simultaneously perform sputtering under different power supply control to form the transition layer on the polymer layer; When the thermal expansion coefficient of the polymer layer is higher than that of the metal layer, the method at least includes the following steps: spin coating raw materials with different concentration ratios using a spin coating method to form the transition layer on the polymer layer.
7. A battery, characterized in that: The composite current collector comprises the composite current collector according to any one of claims 1 to 5 or the composite current collector prepared by the preparation method according to claim 6.
8. A battery module, characterized in that: A battery comprising the battery of claim 7.
9. An electrical device, characterized in that: The invention comprises the composite current collector according to any one of claims 1 to 5, or the composite current collector prepared by the preparation method according to claim 6, or the battery according to claim 7, or the battery module according to claim 8.
Citation Information
Patent Citations
Aluminum alloy composite material and preparation method thereof
CN116411326A
Gradient transition composite tantalum carbide coating and preparation method thereof
CN119710620A